SIKAP PETANI TERHADAP PROGRAM TAMAN TEKNOLOGI PERTANIAN (TTP) BANTURUNG GARING HANTAMPUNG DI KELURAHAN BANTURUNG KECAMATAN BUKIT BATU - Marintan Naibaho; Eka Nor Taufik; Betrixia Barbara (Program Studi Agribisnis Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Palangka Raya, 2019)
The purpose of this research is to study the attitudes of farmers to the program of agricultural technology park (TTP) and to know the problems experience by farmers in Banturung Village, Bukit Batu Subdistrict. The method used in data collection in this study is by using the interview method with the help of questionnaires. This research was conducted in Banturung Village, Bukit Batu subdistrict. The results of this study indicate the attitude of farmers towards the TTP program is included in doubt category. This attitude is influenced by three components of attitude which are divided into nine variable indicators that is:The attitude of farmers towards technology which is classified as